2022
DOI: 10.1002/eat.23787
|View full text |Cite
|
Sign up to set email alerts
|

Examining associations between symptoms of eating disorders and symptoms of anxiety, depression, suicidal ideation, and perceived family functioning in university students: A brief report

Abstract: Objective We examined the relationships between eating disorders symptoms (EDs), suicidal ideation, depressive and anxiety symptoms, and perceived family functioning in a sample of university students aged 18–25 years (N = 397). Method Assessment of symptoms was carried out with the Eating Disorder Diagnostic Scale, Beck Anxiety Inventory and Beck Depression Inventory, among others. We explored the associations between the domains using network analysis. Results We found that physical anxiety symptoms, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
1
1
0
1
Order By: Relevance
“…Through our analysis, we identified several crucial symptoms and edges, which offer potential targets and pathways for interventions. The observed comorbidity between EDs and depression partially aligns with the findings from a network analysis conducted among Chilean university students ( 44 ), which additionally highlighted the central role of physical anxiety symptoms in EDs.…”
Section: Discussionsupporting
confidence: 81%
“…Through our analysis, we identified several crucial symptoms and edges, which offer potential targets and pathways for interventions. The observed comorbidity between EDs and depression partially aligns with the findings from a network analysis conducted among Chilean university students ( 44 ), which additionally highlighted the central role of physical anxiety symptoms in EDs.…”
Section: Discussionsupporting
confidence: 81%
“…En Cuba, un estudio encontró que aquellos que presentaron conducta suicida tuvieron puntuaciones más altas en las variables de depresión e ideación suicida (28). Asimismo, estudiantes universitarios chilenos presentaron asociaciones específicas entre los síntomas de ansiedad física, los síntomas depresivos cognitivos y físicos, los síntomas de trastornos alimentarios y la ideación suicida (29). En Colombia, los factores asociados con la ideación suicida fueron la desesperanza y la depresión (15).…”
Section: Factores Individualesunclassified
“…According to the family system theory, the family is composed of several subsystems, which are both interrelated and restricted to each other, so as to make the whole family operate effectively. Previous studies have shown that family function is an important predictor of individual PTSD, depression, and anxiety ( 34 36 ), and a favorable family environment and parental support can play a protective role in adolescent PTG ( 37 ). The risks posed by COVID-19 have a negative impact on family wellbeing.…”
Section: Introductionmentioning
confidence: 99%